(untitled) (Jurnal Pustaka, 2026)
Cities have denser buildings and over time will continue to experience density. So this has an impact on the availability of empty land being reduced. Due to the increasing amount of empty land due to dense population in urban areas, efforts are needed to increase public knowledge about cultivating vegetables through hydroponics. This research uses the literature study method. The author uses several sources such as journals, articles and relevant documents in accordance with this research study. The research results show that community empowerment activities by using yards to cultivate vegetables through hydroponics are suitable for urban areas because land is limited so that it can help provide knowledge to the community to remain productive through hydroponic vegetable cultivation